ANALYSIS OF REDUPLICATION IN NOVEL MANUSCRIPT “HAFALAN SHALAT DELISA” BY TERE LIYE'S - Adinda Putri Maharani; Cahaya Mutiara brBarus; Siti Nur Halimah; Jusuf Gatra Ginting; Rezky Khoirina Tarihoran (Fakultas Sastra UMN AL Washliyah, 2023)
This study aims to find out what reduplications are contained in the novel “HAFALAN SHALAT DELISA” by TereLiye, which was published for the first time by Republika Publisher, in 2005. Novel “HAFALAN SHALAT DELISA” tells about Delisa (ChantiqSchagerl), a cheerful little girl who lives in Lhok Nga, a small village on the coast of Aceh, is the youngest child. On December 26, 2004, Delisa and Ummi were preparing for a prayer practice exam when suddenly an earthquake occurred which caused Ummi and Delisa's older siblings to die. The method used in this research is a qualitative method with a descriptive type. The results of this study indicate that there are 4 types of reduplication in the novel “HAFALAN SHALAT DELISA” by TereLiye, namely Dwilingga, Dwipurwa, Dwilingga copying the sound and Repeating or repeated repetition. The most dominant reduplication is Dwilingga with a total of 172 words, repeated words with a number of 107 words, Dwilingga copying sounds, there are 4 words for changing vowels and 7 words for changing consonants, then the fourth and the least finding is found in the novel “HAFALAN SHALAT DELISA” is Dwipurwa with findings of 3 words.